Effect of advanced footwear technology spikes on sprint acceleration: A multiple N-of-1 trial - Bernuz, B.; Laujac, S.; Sirial, C.; Auffret, S.; Preda, C.; Slawinski, J.; Millot, B.; Pradon, D.; Coudrat, L.; Gavarry, O. (Sports Medicine - Open, 2024)
Background In contrast with Advanced Footwear Technology-AFT running shoes for long-distance, little is known about AFT sprint spikes on performance and acceleration parameters. However, their use has become widespread since the Tokyo 2020 Olympics, and knowledge of their effects would seem to be an essential starting point before any clinical or socio-economic considerations.